Membrane-supported 1D MOF hollow superstructure array prepared by polydopamine-regulated contra-diffusion synthesis for uranium entrapment. (October 2019) - Yu, Boxuan; Ye, Gang; Chen, Jing; Ma, Shengqian
Abstract: This work reports the architecture of a novel class of membrane-supported 1D MOF hollow superstructures, by using the bio-inspired polydopamine (PDA) mediated contra-diffusion synthetic strategy, for facile and efficient separation of uranium in a flow-through mode. PDA chemistry was firstly employed to modify the inner surfaces of the cylindrical pore channels of polycarbonate track-etched membrane (PCTM), thereby regulating the heterogeneous nucleation and interfacial growth of ZIF-8 crystals. ZIF-8 hollow superstructures embedded in membrane matrix with well-defined 1D channels were obtained. These membrane-supported MOF hollow superstructures then, for the first time, served as integrated chromatographic micro-column arrays for effective entrapment of uranium from aqueous solutions. It is highlighted that the PCTM supported ZIF-8 superstructures exhibited outstanding uranium entrapment ability in both traditional batch mode (capacity 62.3 mg/g) and fast flow-through mode (removal rate over 90% for 3 level). Moreover, new insights into the interaction between ZIF-8 and uranyl ions were obtained, suggesting that an ion-exchange mechanism involved synergistic effect was responsible for uranium binding, especially in a long-term exposure. The membrane-supported 1D MOF hollow superstructures developed in this work represent a new category of organic-inorganic composite membrane. And, it is envisioned that the methodology established in this work would be versatile for preparing more MOF superstructures with deployable form for separation applications. In summary, a novel class of membrane-supported ZIF-8 hollow superstructure was fabricated for effective separation of uranyl ions. Graphical abstract: A novel class of membrane-supported ZIF-8 hollow superstructure, fabricated by polydopamine-mediated contra-diffusion synthesis, serves as integrated chromatographic micro-column arrays for effective separation of uranyl ions. Image 1 Highlights: New membrane-supported 1D MOF hollow superstructures for facile uranium separation. Novel strategy using bio-inspired polydopamine mediated contra-diffusion synthesis. Efficient uranium entrapment and good reusability. New insights into the interaction between MOFs and uranyl ions.